2010
DOI: 10.1128/jb.01350-09
|View full text |Cite
|
Sign up to set email alerts
|

ClpP of Streptococcus mutans Differentially Regulates Expression of Genomic Islands, Mutacin Production, and Antibiotic Tolerance

Abstract: Streptococcus mutans is the primary etiological agent of human dental caries and, at times, of infective endocarditis. Within the oral cavity, the pathogen is subjected to conditions of stress. A well-conserved protein complex named ClpP (caseinolytic protease) plays a vital role in adaptation under stress conditions. To gain a better understanding of the global role of the ClpP protease in cellular homeostasis, a transcriptome analysis was performed using a ⌬clpP mutant strain. The expression levels of more t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 52 publications
2
72
1
Order By: Relevance
“…Deferred antagonism assays confirmed the microarray results and revealed that both DclpP and DclpX were unable to inhibit growth of mutacin IV-and mutacin V-sensitive strains. Despite the limited overlap of genes found to be differentially expressed in our DclpP microarrays and in a previous report (Chattoraj et al, 2010), it is interesting to note that the data regarding expression of bacteriocin-related genes and bacteriocin production between both studies were in full agreement.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Deferred antagonism assays confirmed the microarray results and revealed that both DclpP and DclpX were unable to inhibit growth of mutacin IV-and mutacin V-sensitive strains. Despite the limited overlap of genes found to be differentially expressed in our DclpP microarrays and in a previous report (Chattoraj et al, 2010), it is interesting to note that the data regarding expression of bacteriocin-related genes and bacteriocin production between both studies were in full agreement.…”
Section: Discussionsupporting
confidence: 69%
“…Clp-dependent proteolysis is of particular relevance in Streptococcus, as this genus lacks other known cytoplasmic proteases, such as Lon and ClpYQ (Kajfasz et al, 2009). In fact, proteolysis mediated through ClpXP is an important trait for stress tolerance, gene regulation and virulence in several Gram-positive pathogens (Chastanet et al, 2001;Chattoraj et al, 2010;Frees et al, 2003Frees et al, , 2004Gaillot et al, 2000;Ibrahim et al, 2005;Kwon et al, 2004). Previously, we demonstrated that a number of virulence properties of S. mutans, including stress tolerance, biofilm formation and colonization in a rodent caries model, were influenced by ClpXP proteolysis (Kajfasz et al, 2009 Here, we used microarrays to better understand the global effects of ClpXP proteolysis in S. mutans.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of SprV causes an increase in the transcript levels of clpP. Our laboratory has previously shown that ClpP is involved in mutacin production, antibiotic stress tolerance, and control of gene expression from TnSmu1 and TnSmu2 genomic islands (31). Although our transcriptomic data aligned with the observed phenotypes, it was impossible to predict how SprV affects gene expression because of the largely interconnected pathways affecting these cellular processes.…”
Section: Figsupporting
confidence: 45%
“…In Thermus thermophilus, phage infections induce the transcription of cas genes and CRISPR arrays by a sensing mechanism using the cell's cyclic AMP receptor proteins (301,302). Stress, such as phage infection, the accumulation of misfolded proteins in the E. coli membrane, or the absence of ClpP in Streptococcus mutans, can also activate the expression of certain Cas proteins (303,304).…”
Section: Genetic Elements Controlling the Stability Of Mobile Elementsmentioning
confidence: 99%